Arte de España y México - Fairbanks, Tess (My University, 2023)
Throughout the Spring 2023 semester, I took Dr. Bender’s graduate-level course “SPAN 779: Art of Spain & Mexico in the L2 Classroom.” By taking this course I gained a better understanding of using Content Based Instruction and of utilizing authentic artwork from Spain and Mexico within the classroom. I implemented this knowledge in the classroom, through student teaching, and reflected on its value for future teaching. This project consists of three sections. The first section is a thematic, virtual gallery-map of relevant artwork which will serve as a resource for my current and future practice. The next is the creation a thematic lesson planning unit which centers around the art within the gallery-map. Finally, is the implementation ofthis unit within my student teaching placement and the evaluation of the efficacy of the strategies utilized. The goal of this project is to investigate and implement strategies which will inform my future teaching.